2020
DOI: 10.1186/s13054-020-2826-6
|View full text |Cite
|
Sign up to set email alerts
|

Hyperoxemia and excess oxygen use in early acute respiratory distress syndrome: insights from the LUNG SAFE study

Abstract: Background: Concerns exist regarding the prevalence and impact of unnecessary oxygen use in patients with acute respiratory distress syndrome (ARDS). We examined this issue in patients with ARDS enrolled in the Large observational study to UNderstand the Global impact of Severe Acute respiratory FailurE (LUNG SAFE) study. Methods:In this secondary analysis of the LUNG SAFE study, we wished to determine the prevalence and the outcomes associated with hyperoxemia on day 1, sustained hyperoxemia, and excessive ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 49 publications
0
18
2
3
Order By: Relevance
“…A sub-study from the epidemiological LUNG SAFE study (from 2016) assessed the association of hyperoxemia (on admission or sustained) and excessive oxygen use in early ARDS. In this cohort study, no relationship could be found to worse outcome in regard to hypoxemia and high FiO 2 ( Madotto et al, 2020 ). Generally, hyperoxia (and mild hyperoxia) aggravate and synergistically worsen VILI phenomenons such as an increase in pulmonary permeability and edema formation, decreased surfactant and lung compliance, and an increase in inflammatory markers and apoptosis ( Kallet and Branson, 2016 ) (and references therein).…”
Section: Therapeutic Strategies: Where Do We Stand and What Is The Fucontrasting
confidence: 53%
“…A sub-study from the epidemiological LUNG SAFE study (from 2016) assessed the association of hyperoxemia (on admission or sustained) and excessive oxygen use in early ARDS. In this cohort study, no relationship could be found to worse outcome in regard to hypoxemia and high FiO 2 ( Madotto et al, 2020 ). Generally, hyperoxia (and mild hyperoxia) aggravate and synergistically worsen VILI phenomenons such as an increase in pulmonary permeability and edema formation, decreased surfactant and lung compliance, and an increase in inflammatory markers and apoptosis ( Kallet and Branson, 2016 ) (and references therein).…”
Section: Therapeutic Strategies: Where Do We Stand and What Is The Fucontrasting
confidence: 53%
“…Oxygen targets and the risk of hyperoxemia are emerging issues in critically ill patients. 17 , 18 To the best of our knowledge, neither incidence nor impact of hyperoxemia during interhospital transfers has been explored. Based on our experience, it is hard to be in strict compliance with strict oxygenation targets during medevac flights, and the risk-to-benefit ratio may favor the prevention of hypoxemia in this context.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia is common in patients receiving MV for ARDS. A secondary analysis of the LUNG SAFE trial [ 32 ] reported that 30% of the 2005 analyzed patients had hyperoxia on day 1, and 12% had sustained hyperoxia. While two randomized controlled trials found beneficial effect of avoiding hyperoxia [ 33 , 34 ], a recent large international multicenter trial demonstrated no effect of conservative oxygen therapy in a cohort of critically ill patients [ 35 ].…”
Section: Pathophysiologymentioning
confidence: 99%